2017
DOI: 10.1038/leu.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

The mutational oncoprint of recurrent cytogenetic abnormalities in adult patients with de novo acute myeloid leukemia

Abstract: Recurrent chromosomal abnormalities and gene mutations detected at the time of diagnosis of acute myeloid leukemia (AML) are associated with particular disease features, treatment response and survival of AML patients, and are used to denote specific disease entities in the World Health Organization classification of myeloid neoplasms and acute leukemia. However, large studies that integrate cytogenetic and comprehensive mutational information are scarce. We created a comprehensive oncoprint of mutations assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 48 publications
(70 reference statements)
16
79
0
Order By: Relevance
“…To obtain more detailed insights into the mutational patterns associated with the 17-gene LSC signature, we analyzed 81 cancer and leukemia-associated genes. 19 We found that 77 genes were mutated in at least one patient (Online Supplementary Table S4). Patients with a 17-gene low score had fewer mutations compared with patients with a 17-gene high score (median: 2 vs. 3; P<0.001).…”
Section: Mutational Landscape Associated With the 17-gene Leukemia Stmentioning
confidence: 94%
See 2 more Smart Citations
“…To obtain more detailed insights into the mutational patterns associated with the 17-gene LSC signature, we analyzed 81 cancer and leukemia-associated genes. 19 We found that 77 genes were mutated in at least one patient (Online Supplementary Table S4). Patients with a 17-gene low score had fewer mutations compared with patients with a 17-gene high score (median: 2 vs. 3; P<0.001).…”
Section: Mutational Landscape Associated With the 17-gene Leukemia Stmentioning
confidence: 94%
“…We, therefore, derived the 17-gene score from a set of samples from adults with AML and determined associations between the signature and known prognosticators 1,17,18 as well as mutational data of 81 cancer-and leukemia-associated genes. 19 Moreover, we validated the prognostic impact of the 17-gene signature alone and in the context of the 2017 ELN genetic-risk classification. 1…”
Section: Ferrata Storti Foundationmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, next‐generation sequencing (NGS) revealed a unique mutational spectrum associated with TP53 mutation in CK/MK AML. In particular, the mutual exclusivity between TP53 mutations and FLT3 ‐TKD and the rare occurrence of DNMT3A , NPM1 , KRAS , EZH2 , TET2 and SETBP1 have also been reported in different cohorts and may suggest their possible detrimental effects on TP53 mutant cells. NOTCH1 mutations, which are rarely reported in AML, were identified in 16% cases.…”
Section: Discussionmentioning
confidence: 99%
“…While some mutations such as FMS-related tyrosine kinase 3 (FLT3), nucleophosmin (NPM1), and isocitrate dehydrogenase 1 and 2 (IDH1/2) had already been reported in AML, other mutations such as U2AF1 and others involved in spliceosome pathways were discovered. The pattern of AML mutations was subsequently validated in additional cohorts with larger numbers of adult patients (5,10). The presence and prognostic significance of genetic mutations have also been examined in pediatric AML and show trends similar to those of adult AML.…”
Section: Molecular Subgroups Of Aml Have Therapeutic Implicationsmentioning
confidence: 99%